Child Intellectual Development in Relation to Cytokine Levels in Umbilical Cord Blood - von Ehrenstein, Ondine S. (Oxford University Press, 2012)
Although cytokines play a dual role in the developing neurologic system and in prenatal immune reactions, relations between fetal cytokine levels and child intellectual development remain unknown. The authors investigated associations between umbilical cord serum cytokine concentrations and intellectual outcomes in 369 children within a prospective cohort study, the Eunice Kennedy Shriver National Institute of Child Health and Human Development-University of Alabama Infant Growth Study (1985–1988). Concentrations of interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), and interleukins 4, 10, and 12p70 were determined. The Wechsler Preschool and Primary Scale of Intelligence–Revised was administered at age 5 years, producing verbal and performance intelligence quotients (VIQ and PIQ); associations with each cytokine were evaluated using linear and logistic regression. Log-unit increases in IFN-γ (adjusted odds ratio (aOR) = 0.67, 95% confidence interval (CI): 0.46, 0.98) and interleukin-12p70 (aOR = 0.43, 95% CI: 0.21, 0.87) were inversely associated with low PIQ (score <70). One log-unit increase in TNF-α was associated with a reduced odds ratio for low VIQ (score <70) among preterm children (aOR = 0.11, 95% CI: 0.01, 0.94) and an elevated odds ratio for low VIQ among small-for-gestational-age children (aOR = 3.96, 95% CI: 0.99, 15.9). IFN-γ, which is involved in neurogenesis and perinatal adaptive immunity, may be related to fetal neurologic development overall, while TNF-α may be a marker of intellectual development in vulnerable subgroups.